STRATEGIC CHALLENGES OF DIGITAL TRANSFORMATION FOR STATE UNIVERSITIES. A UNIVERSITY SOCIAL RESPONSIBILITY - Gaete Quezada, Ricardo (Profesorado, Revista de Currículum y Formación del Profesorado, 2023)
Currently, modern societies are characterized by the intensive use of new digital technologies in different spheres of daily life, or free access to large volumes of data available on the Internet, among other features. Thus, a key challenge for university social responsibility will be to perform missionary functions with greater social relevance, seeking to respond to the social needs and requirements of the 21st century. The objective of the article is to analyze the strategic challenges of the digital transformation process of Chilean state universities, through a quantitative research design, a documentary analysis of the main planning instruments of the institutions included in the study is developed, observing that the majority of The universities analyzed partially incorporate some aspects for digital transformation, especially those related to the possession of greater knowledge and information for institutional decision-making. The main conclusion is that the new normative framework of Chilean higher education and the social effects of the covid-19 pandemic are transformed into a disruptive opportunity to advance more effectively in the digital transformation of university work with a systemic approach to public policy.